Clinical Features of and Risk Factors for Rhabdomyolysis Among Adult Patients with Dengue Virus Infection - Huang, Shi-Yu (Am J Trop Med Hyg, 2015)
Among 1,076 dengue patients, 9 patients with rhabdomyolysis and 1,067 patients without rhabdomyolysis (controls) were retrospectively analyzed. Of nine patients with rhabdomyolysis, the most commonly reported symptom other than fever was myalgia; dengue hemorrhagic fever (DHF) was found in seven cases, and acute kidney injury was found in six cases. Furthermore, one (11.1%) patient died. The median duration from hospital admission to rhabdomyolysis diagnosis was 3 days. Patients with rhabdomyolysis had higher age, proportion of men, prevalence of hypertension, frequency of myalgia, and incidences of DHF, pleural effusion, and acute kidney injury than controls. Multivariate analysis showed that hypertension (odds ratio [OR] = 14.270), myalgia (OR = 20.377), and acute kidney injury (OR = 65.547) were independent risk factors for rhabdomyolysis. Comparison of cytokine/chemokine concentrations in 101 DHF patients, including those with (N = 4) and without (N = 97) rhabdomyolysis, showed that interleukin-6 and tumor necrosis factor-α levels were significantly increased in the former.